Adsorption of Zinc(II) from Aqueous Solution Using Poly(ethylene terephthalate)-Grafted-Methyl methacrylate/Acrylic Acid - Azizinezhad, Fariborz (Asian Journal of Chemistry, 2013)
In the present study, graft copolymerization of methyl methacrylate, acrylic acid onto poly(ethylene terephthalate) fibers has been studied as a new adsorbent for the removal of Zn2+ ions from aqueous solutions by a batch equilibrium technique. The prepared copolymer was characterized by scanning electron microscopy, specific surface area, cation exchange capacity and point of zero charge (pHzpc). The best conditions for removal of Zn2+ recorded (pH = 6.5, t = 20 min, maximum adsorption capacity = 17.00 mg/g).